CDK4/6 Inhibitors in the Management of Hormone Receptor‐Positive (HR+)/Human Epidermal Growth Factor Receptor 2‐Negative (HER2−) Advanced Breast Cancer in Indonesia: Challenges, Opportunities, and Recommendations - Sonar Soni Panigoro; Samuel J. Haryono; Prihantono Prihantono; Dedy Hermansyah; Sumadi Lukman Anwar; Yohana Azhar; Febriyanto Kurniawan; Putu Anda Tusta Adiputra; Kristanto Yuli Yarso; Asdi Wihandono (Asia-Pacific Journal of Clinical Oncology, 2026)
ABSTRACT Breast cancer (BC) is the most prevalent cancer affecting women globally, with Asia accounting for nearly half of all cases. BC represents a major public health issue, particularly in Indonesia, where it is the leading cancer type among women. Indonesia faces high rates of late‐stage diagnoses and poor survival outcomes, largely driven by socioeconomic disparities, limitations in healthcare infrastructure, and delays in detection; challenges also encountered across comparable resource‐constrained settings. Hormone receptor‐positive (HR+)/human epidermal growth factor receptor 2‐negative (HER2˗) advanced breast cancer (ABC) remains challenging to manage due to the lack of curative treatment options. Current therapeutic strategies focus on prolonging survival and enhancing quality of life. In this context, cyclin‐dependent kinase (CDK)4/6 inhibitors have emerged as a major advancement, significantly improving progression‐free and overall survival in selected settings when used in combination with endocrine therapy (ET). The CDK4/6 inhibitors palbociclib, ribociclib, and abemaciclib have shown notable efficacy in Asian populations, despite a higher incidence of hematological toxicities. However, access to these therapies remains limited in Indonesia because they have not yet been incorporated into national treatment guidelines. This review underscores the critical role of CDK4/6 inhibitors in the treatment of HR+/HER2˗ ABC, with a particular focus on Indonesian patients. It supports consideration of these agents for inclusion in national clinical guidelines to enhance patient outcomes. Evidence‐informed recommendations endorse their use in patients with ET‐sensitive tumors and as a potential alternative to chemotherapy in selected aggressive cases involving visceral disease without immediately life‐threatening organ dysfunction. Addressing the barriers to early diagnosis and expanding access to advanced therapies is crucial for improving BC management in Indonesia and comparable settings.